2004
DOI: 10.1128/cdli.11.1.152-160.2004
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and Mucosal Responses to Oral Administration of Excretory and Secretory Antigens fromGiardia intestinalis

Abstract: Giardia, a flagellated protozoan that infects the upper small intestine of its vertebrate host, is the most common parasitic protist responsible for diarrhea worldwide. Molecules released by the parasite, particularly excretory and secretory antigens, seemed to be associated with pathogenesis as well as with the expression of Giardia virulence. In the present work, we examined the effect of oral administration of Giardia intestinalis excretory and secretory antigens on systemic and local antibody response as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 57 publications
(42 reference statements)
8
45
0
4
Order By: Relevance
“…This is supported by similar observations in previous reports with other substrates and the P1 strain (Hare et al 1989, Parenti 1989. Mining of the Giardia Genome Project based on a clone (A6) from WB strain (http://www.embl.edu/Giardia) revealed at least 7 well characterized genes for giardial cysteine proteases while the deduced open reading frames for other putative proteases predicted only serine and metallo but not aspartic-type proteases.Our findings are also consistent with the detection of proteolytic activity in E/S products from trophozoites of the P1 strain (Jiménez et al 2000(Jiménez et al , 2004. However an enhancement of protease secretion during trophozoites-IEC6 interaction has not been previously reported.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…This is supported by similar observations in previous reports with other substrates and the P1 strain (Hare et al 1989, Parenti 1989. Mining of the Giardia Genome Project based on a clone (A6) from WB strain (http://www.embl.edu/Giardia) revealed at least 7 well characterized genes for giardial cysteine proteases while the deduced open reading frames for other putative proteases predicted only serine and metallo but not aspartic-type proteases.Our findings are also consistent with the detection of proteolytic activity in E/S products from trophozoites of the P1 strain (Jiménez et al 2000(Jiménez et al , 2004. However an enhancement of protease secretion during trophozoites-IEC6 interaction has not been previously reported.…”
supporting
confidence: 81%
“…In addition, the presence of cysteine protease activities in excretory/secretory (E/S) products of P1 strain has also been reported (Jiménez et al 2000). These E/S products are associated with mucosal injuries observed in murine giardiasis (Jiménez et al 2004). However the possible relation between protease secretion and the adhesion of G. duodenalis to epithelial cells has not been tested.…”
Section: Protease Secretion By Giardia Duodenalis Trophozoites Upon Imentioning
confidence: 99%
“…It is possible that these fragments interfered with the identification of the 58 kDa protein. Moreover, several unknown proteins with masses ranging from 15 to 225 kDa as well as unidentified proteins with cysteine-type protease activity have been reported in supernatants of Giardia-host cell co-cultures [15,33,34]. This is the first time giardial ADI, OCT and enolase have been shown to be present in Giardia culture supernatants.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study also demonstrated that the excretory-secretory products (ESP) of G. lamblia contained major antigen(s) responsible for protection against infection in mice ( Kaur et al, 1999Kaur et al, , 2001. Oral administration of G. lamblia ESPs into BALB/c mice stimulated a Th2 response, which led to intestinal histological changes characterized by eosinophilic infiltration, and can induce host cell apoptosis, hypercellularity, and enterocytic desquamation (Jiménez et al, 2004). Glycoproteins in G. lamblia ESP were found to induce antibody production during giardiasis (Jiménez et al, 2007).…”
Section: Exosome and Microvesicles Content Can Alter Neighbouring Cellsmentioning
confidence: 98%
“…Most likely, mechanical effects, or some other, as yet not described mechanism, produces villus and brush border microvillus atrophy, leading to digestive enzyme deficiencies (Solaymani-Mohammadi and Singer, 2011), and chronic giardiasis can lead to mucosal inflammation with pronounced villus loss (Hanevik et al, 2007); protease activities may be a direct cause of diarrhoeas in giardiasis. Moreover, Jiménez et al (2004) found that excretory and secretory antigens (E/S Ags) from G. lamblia induced an intestinal pathogenesis, which coincided with mucosal inflammation in BALB/c mice. Oral administration of the E/S Ags not only stimulated production of antibodies with parasiticidal activity, but also resulted in histological alterations within the intestinal tissue that were comparable to those observed in natural and experimental Giardia infections (Jiménez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%